Bergson in San Junipero: Corporality, simulation and memory - Soto Chaves, Alejandro (Escritura e Imagen, 2021)
Bergsonian philosophy held prominence in the Western philosophical debate during the last decade of the 19th century and, at least, the first two decades of the 20th century. In this article, despite the relative poor regard devoted to Henri Bergson’s thought nowadays, his theory of memory is carefully examined, in the light of the most recent research on his work, problematizing his concepts of image, habit, perception, time and memory, with the ulterior purpose of displaying the conceptual apparatus wielded by Bergson in the critical reading of the ideas underlying the fourth episode (third season) of the renowned British television anthology series Black Mirror, namely, San Junipero (2016); which aims to offer a reflection on the memory-nostalgia dyad and the memory-technology-simulation triad (that is, a panoramic proposal for the demarcation of Bergsonian metaphysical limits with respect to contemporary topics such as virtual reality, cyborg theory and posthumanism).